Clinical Trial Access in Low- and Middle-Income Countries: A Case Study on India. (21st October 2021) - Desai, Aakash; Sirohi, Bhawna; Mathew, Aju
Abstract: The global burden of cancer is estimated to be more than 20 million cases by 2030, the majority occurring in low- and middle- income countries (LMICs). LMICs account for 64% of global cancer deaths and 80% of disability-adjusted-life-years lost. Despite this, only 5% of the global cancer resources are spent in LMICs causing a high mortality-to-income ratio. Despite the burgeoning number of clinical trials in the HICs, there are several reasons to conduct clinical trials in LMICs. In this commentary, we discuss the problem of access to clinical trials in LMICs using India as a case study.